The half-century odyssey of regulatory B cells: from Breg discovery to emerging frontiers - Zheremyan, Elina A.; Kon, Nikolai R.; Ustiugova, Alina S.; Stasevich, Ekaterina M.; Bogomolova, Elvina A.; Murashko, Matvey M.; Uvarova, Aksinya N.; Demin, Denis E.; Kuprash, Dmitry V.; Korneev, Kirill V. (Frontiers in Immunology, 2025)
For half a century, the quiet work of a specialized immunosuppressive B cell subset has been slowly unveiled, revealing its profound impact on immune balance. This review provides a comprehensive retrospective on the history of regulatory B cell (Breg) investigation, tracing their journey from initial elusive observations to their current recognition as crucial immunomodulators. We explore the paradigm shift from B cells solely as antibody producers to their multifaceted roles in immunosuppression. Key milestones include the earliest suggestions of suppressive B cell activity around 1970, the formal coining of the currently used term "regulatory B cells" in the early 2000s, and the subsequent elucidation of diverse Breg subsets and their suppressive mechanisms. Finally, we discuss contemporary advances, including the application of single-cell multi-omics, the identification of novel markers and metabolic regulators, and the promising yet challenging path toward Breg-based therapeutic strategies. This historical perspective underscores the remarkable progress in Breg biology and illuminates future directions for harnessing their clinical potential.